Interpretasi Filogenetik Ular-Ular Anggota Familia Colubridae - Annawaty Idris (Biocelebes, 2007)
The aim of this research is study about filogenetic interpretation of colubride snake based on structure of rear fang and skeleton components.The twelve species the colubride snake was giving life for. This research was conducted by observed  of  rear  fang  character  and  skeleton  components,  include  os  frontal,  parietal,  maxilla, palatine, pterygoide, quadrates, basi-parasphenoide and basioccipitaleBased  on  the  similarity  and  difference  of  taxonomic  characters,  this  research  can  assumed that filogenetic position of twelve colubride species divided in three groups. The first groups consist of primitive colubride i.e:  Elaphe flavolineata, Elaphe radiate, Elaphe oxycephala, Dendrelaphis pictus, Ptyas  korros,  Ptyas  mucosus,  Natrix  piscator,  Natrix  subminiata  and  Natrix  vittata.  The  second consist of only one species, Boiga dendrophila. The most advance group consists of  E. enhydris dan H. buccata.